The safety of intelligent driver support systems : design, evaluation, and social perspectives - Barnard, Yvonne F.; Krems, Josef, 1954-; Risser, Ralf (Human factors in road and rail transport., 2011)
Road telematics and driver assistance systems offer a real opportunity to aid mobility and road safety. However, they also raise numerous questions. Problems related to the design and evaluation of intelligent driver support systems (IDSSs) and social perspectives related to their large scale introduction may only be fully addressed from a multi-disciplinary viewpoint. People from both engineering and social sciences, should be involved and this book provides such knowledge from both a human and social factors perspective.